An unploughed reference pedon of Luvic Greyzemic Phaeozem under an old-growth forest in the long-cultivated North Pritom’e region in south-east Western Siberia - Kuzmina, Daria M.; Tkacheva, Anastasia A.; Loiko, Sergey V.; Istigechev, Georgy I.; Kulizhsky, Sergey P. (Acta Biologica Sibirica, 2026)
This study presents a morphological and analytical characterisation of a native reference soil developed under a old-growth, non-agrogenic tall herb aspen forest in the south-eastern part of Western Siberia’s forest zone. The main objective was to establish a baseline description of a Luvic Greyzemic Phaeozem, the vast majority of whose analogues in the region have been converted to arable land. Conducted at the ’Ust-Sosnovka’ key site, the research employed detailed profile descriptions, morphometric analyses and a range of laboratory methods, including carbon elemental analysis, carbonate determination and sub-micromorphological investigations of carbonate pedofeatures. The results revealed a thick, well-structured and highly biogenic soil profile, characterised by a pronounced accumulative distribution of organic carbon (C_(org) reaching 5.2–9.9% in the 0–10 cm layer) and low bulk density (0.6–0.7 g/cm³), which is indicative of intense bioturbation. A significant stock of inorganic carbon (Cinorg) was identified in the middle and lower horizons, with neoformations showing signs of active dissolution and leaching under the humid climate. The soil is classified as prograding, with no signs of degradation or relic features. The calculated carbon stocks emphasise the importance of both the surface and deep horizons in the total carbon budget. The characterised pedon serves as a crucial reference for quantifying the direction and magnitude of centennial-scale agrogenic transformation in analogous soils. The findings emphasise the importance of conserving such native ecosystems for monitoring carbon stocks and assessing the sustainability of land management. Consequently, this soil should be included in regional soil protection registries, such as a prospective Red Book of Soils for the Kuzbass region.